Identification and characterization of a Masculinizer homologue in the diamondback moth, Plutella xylostella - Harvey-Samuel, T; Norman, VC; Carter, R; Lovett, E; Alphey, L (Wiley, 2019)
Recently, a novel sex‐determination system was identified in the silkworm (Bombyx mori) in which a piwi‐interacting RNA (piRNA) encoded on the female‐specific W chromosome silences a Z‐linked gene (Masculinizer) that would otherwise initiate male sex‐determination and dosage compensation. Masculinizer provides various opportunities for developing improved genetic pest management tools. A pest lepidopteran in which a genetic pest management system has been developed, but which would benefit greatly from such improved designs, is the diamondback moth, Plutella xylostella. However, Masculinizer has not yet been identified in this species. Here, focusing on the previously described ‘masculinizing’ domain of B. mori Masculinizer, we identify P. xylostella Masculinizer (PxyMasc). We show that PxyMasc is Z‐linked, regulates sex‐specific alternative splicing of doublesex and is necessary for male survival. Similar results in B. mori suggest this survival effect is possibly through failure to initiate male dosage compensation. The highly conserved function and location of this gene between these two distantly related lepidopterans suggests a deep role for Masculinizer in the sex‐determination systems of the Lepidoptera.